IMPLEMENTATION OF ICT-BASED ON CONTEXTUAL LEARNING TO IMPROVE STUDENTS’ WRITING SHORT STORY AT ELEVENTH GRADE OF PADALARANG 2 SENIOR HIGH SCHOOL - Ai - Mulyati; Euis Eti Rohaeti (IKIP Siliwangi, 2018)
Class action research aims to describe the application of ICT-based contextual learning strategies to improve students ' ability in writing short stories. The subject in this study are students of Class SMA. The data were analyzed using descriptive quantitative and qualitative descriptive. Based on the results of this study, it can be concluded the implementation of ICT-based contextual learning strategies can improve writing skills. The application of contextual learning ICT-based learning writing get positive response from students. Students can write a short story with the correct steps. Therefore, these researchers are advised to implement ICT-based contextual learning strategy, as one of the learning strategies, on subjects in other languages in General and on the Indonesian Language lesson.